Improving Students’ L2 Writing through Teacher’s Written Corrective Feedback - Tinsi Ayu Feren; Abdul Halim; Azwar Abidin (IAIN KENDARI, 2020)
This qualitative study aims to improve students’ writing skill through teacher’s written corrective feedback based on 12 students’ writing at one of vocational schools in Kendari. It is expected that the students’ writing skill can be improved, and the students can participate actively in the English teaching and learning process. The instrument used in this study is documentation of students’ writing from the first draft until the third draft. To analyze the data, the researcher uses Creswell’s frame in 2009, such as: the data, displaying the data and concluding the data. The result of the study reveals that most of students improve their writing skill after being given teacher’s written corrective feedback and in the third draft, they make less mistake than the first draft. This study implies that, the use of teacher’s written corrective feedback in writing activity should be encouraged to improve the students’ writing ability.Keywords: Feedback; Qualitative; Teacher; Writing.